Influence Capital Structure, Liquidity, Size the Company, Debt Policy and Profitability towards Corporate Value on Property Company, Real Estate and Building Construction Listed on the Stock Exchange Indonesia Period 2016-2019 - Ninta Katharina; Albert Wijaya; Juliana Juliana; Valen Avelina (Budapest International Research and Critics University, 2021)
Property issuers must be prepared to face another year of sluggish market where after three years there has been a continuous cycle of weakness. The purpose of this research is to see the influence. Capital Structure, Liquidity, Company Size, Debt Policy and Profitability against Company Value in property companies, re-evaluation and construction of buildings listed on the Indonesia Stock Exchange for the 2016-2019 Period. Quantitative research approach. This type of descriptive quantitative research. The nature of this research is due and effect / causal. The population in this study were 83 types of property, real estate, and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 Period. The sample is 23 companies. The result is that the capital structure has no partial effect on company value in companies, real estate and building construction listed on the Indonesia Stock Exchange for the 2016-2019 Period. Liquidity does not partially affect the value of property, real estate and building construction companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The size of the company does not have a partial effect on the value of the company in property, real estate and building construction listed on the Indonesia Stock Exchange for the 2016-2019 period. The debt policy does not have a partial effect on company value in property, real estate and building construction listed on the Indonesia Stock Exchange for the 2016-2019 period. Profitability has a partial effect on company value in property, real estate, and building construction listed on the Indonesia Stock Exchange for the 2016-2019 period. Capital structure, liquidity, company size, debt and profitability simultaneously influence the value of the company in property, real estate and building construction listed on the Indonesia Stock Exchange for the 2016-2019 period.